Literature Analysis on the Impact of Gamified Education on Engagement, Motivation, and Learning Outcomes Among Preschool Children in Rural Communities in China - You, Xinni; Sanmugam , Mageswaran (CV Media Inti Teknologi, 2024)
This study explores the impact of gamified education on preschool children in rural communities, focusing on engagement, motivation, and learning outcomes. Gamification, the application of game design elements in non-game contexts, has shown positive effects in educational settings, particularly in enhancing student motivation and engagement. However, its application in rural communities, characterized by limited educational resources, remains underexplored. This research investigates how gamified learning can address the educational challenges faced by rural preschool children, integrating local cultural elements to improve learning experiences. A quasi-experimental design was employed, with an experimental group engaging in gamified learning activities based on rural culture and a control group receiving traditional instruction. The study utilized a mixed-methods approach, including surveys, direct observations, and interviews with teachers, parents, and children, to assess learning motivation, engagement, and academic outcomes. Results indicated that children in the gamified learning group showed higher levels of participation, motivation, and academic achievement compared to those in the control group. Furthermore, incorporating traditional rural games into the gamification process not only increased engagement but also helped preserve local cultural heritage. Despite challenges such as limited digital infrastructure, the study highlights the potential of gamification to promote learning and cultural identity in resource-constrained environments. The findings suggest that gamification, when adapted to local contexts, can significantly enhance the educational experiences of preschool children in rural communities, fostering both academic and cultural development. This study provides valuable insights for future research and educational policy in rural areas.